Is Any Feature of the Stabilometric Evaluation Clinically Relevant in Patients with Temporomandibular Disorders? A Cross-Sectional Study - Raquel Delgado-Delgado; Juan Antonio Valera-Calero; Antonia Emma Gowie; Sofia Olivia Calvo-Moreno; María Belén Centenera-Centenera; Gracia María Gallego-Sendarrubias (Applied Sciences, 2021)
Current neuroanatomical evidence showed the anatomical relationship between the temporomandibular joint innervation with the vestibular system. However, there is no clear evidence regarding if temporomandibular disorders are associated with balance impairments. Therefore, the aims of this study were to assess the clinical relevance of stabilometric features in populations with temporomandibular disorders and to analyze the influence of the mandibular position and visual afference in the balance scores in both healthy and clinical populations. This observational study was conducted in one sample of healthy controls and one sample with temporomandibular disorders. Sociodemographic data (age, gender, height, weight, body mass index, and foot size), clinical data (presence or absence of temporomandibular disorders) and stabilometric data under six different conditions were collected. Sixty-nine subjects (43.5% male; 36.2% patients) were assessed. No differences between Temporomandibular disorders and healthy groups were found in any stabilometric outcomes, unlike oscillation area with closed eyes and medium interscuspidal position (p < 0.01). Although visual feedback showed to be relevant (p < 0.0001), mandibular position produced no differences in any stabilometric measurement (p > 0.05). This study found that healthy subjects and patients with temporomandibular disorders showed no balance differences in the stabilometric outcomes assessed. Although visual input played an important role in the balance, mandibular position seems to be irrelevant.